Beyond the Entwurf: (A Preliminary) Project for a Scientific Death Drive - Chernoff, MLA (Pivot: A Journal of Interdisciplinary Studies and Thought, 2016)
This paper explores the conceptual thresholds of psychoanalysis as they have been laid out over the course of the 20th and 21st centuries, specifically focusing on the tensions between Sigmund Freud and two of his many heirs, viz., Jean Laplanche and Jacques Lacan. First, I extricate Freud's visionary text, Beyond the Pleasure Principle (1920), from Laplanche's condemnation of the text as either whimsically metaphyical or simply a return to Freudian seduction theory. I argue that neither categorization has the capacity to contain the argumentative force of Beyond. Second, by attending to Lacan's theorizations of the philosophy of science apropos of psychoanalysis, I speculate on the possibility of a psychoanalytic future, one that incorporates scientific rigour into its theories practices. By accounting for the materiality of the death drive (through Timothy Morton's object-oriented interpretation of molecular processes), I show how the death drive was never necessarily metaphorical and thereby acts as an discourse-altering facet of psychoanalysis in a way that neither Laplanche nor Lacan could have anticipated.